Remarks on Aymara, Quechua and Puquina words in the Royal Spanish Academy's Dictionary, 23rd edition - Baldoceda Espinoza, Ana (2017)
In this article we have selected a sample of the Royal Spanish Academy's Dictionary of the Spanish Language (23rd edition, 2014) in order to survey words of Aymara, Quechua and Puquina origin which are used in Peru. In analysing these lexical items we take into consideration the following: a) headword; b) entry; c) etymology; d) phonological representation; e) gloss; f) usage label; g) geographical label; h) time label; i) meaning; j) lexemes of native origin not recorded in the 2014 Dictionary of the Spanish Language.